Mashbill and barrel aging effects on the sensory and chemometric profiles of American whiskeys. Issue 2 (24th January 2020) - Phetxumphou, Katherine; Miller, Greg; Ashmore, P. Layton; Collins, Thomas; Lahne, Jacob
Abstract: American whiskeys are economically and culturally significant beverages with complex sensory profiles; however, how aromas and flavours are linked to mashbill (fermentedwash recipe) and/or aging time in new, charred oak barrels have not been thoroughly investigated. To accomplish this goal, sensory Descriptive Analysis and Chemometric analyses, including Headspace Solid‐Phase Microextraction‐Gas Chromatography‐Mass Spectrometry and Liquid Chromatography‐Quadrupole‐Time‐of‐Flight‐Mass Spectrometry, were conducted to evaluate American whiskeys distilled from controlled mashbills (two bourbons, two ryes) and aged in new, charred oak barrels from the same cooperage and stave lot. Data were analysed using M/ANOVA, Canonical Variate Analysis and Multiple Factor Analysis. The trained Descriptive Analysis panel evaluated all samples and developed a consensus attribute list. Panellists rated samples on 15‐pt scales, in triplicate using a Williams Latin Square Design spread over 12 sessions to reduce presentation order effects. Descriptive Analysis results revealed that whiskey samples varied significantly in multivariate profiles and for 18 of 35 attributes by mashbill and aging time at bottling, but not by their interaction. Potentially positive whiskey attributes (e.g., vanilla and apples) are linked to increased aging times and higher corn content whereas other attributes (e.g., vegetal and hay/grassy) are correlated to shorter aging times. All analyses showed similar overall projections in the Multiple Factor Analysis for individual samples. Results from this study can help researchers, consumers, and distillers map sensory profiles of American whiskeys due to mashbill and aging time bottling. © 2020 The Institute of Brewing & Distilling